Jitter and muscle fiber conduction velocity in long COVID fatigue - João Aris Kouyoumdjian; Leticia Akemi Rama Yamamoto; Carla Renata Graca (Arquivos de Neuro-Psiquiatria)
Background Long coronavirus disease (long COVID, LC) is defined as the continuation or development of new symptoms 3 months after the acute stage of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. In LC, the rate of fatigue/postexertional malaise (F-PEM) has been described to be as high as 70%, regardless of age or severity of the acute symptoms.